Evaluation of the occupational safety and health implementation in the informal sector fishermen in South Sumatra Province - Erista, Yola; Prabandari, Yayi Suryo; Sutena, Marthinus (Universitas Gadjah Mada, 2022)
Purpose: This study evaluates the implementation of occupational safety and health (K3) in the informal sector of fishermen in Tanjung Kurung Village, Penukal Abab Lematang Ilir (PALI) Regency, South Sumatra Province. Methods: This qualitative research employs a case study approach. The research was conducted in Tanjung Kurung Village, PALI Regency. Informants included 22 individuals: nine fishermen, nine fishermen's wives, the head of the PALI regency health office, the manager of the UKK post program at the Health Office, the manager of the UKK Post Program at the Abab District Health Center, and the head of Tanjung Kurung Village. Data collection involved in-depth interviews, observations, and document reviews. Results: Implementing K3 in the informal sector of fishermen in Tanjung Kurung Village has been inadequate. Factors influencing this include the persistence of unsafe K3 practices among fishermen, lack of support from relevant parties for K3 management, high K3 risks fishermen face, and the pre-prosperous welfare status of fishermen's families. Common accidents include boat collisions, injuries from fish spines and branches, threats from crocodiles and venomous snakes, machete injuries, and boat sinking due to overloading. Occupational diseases among fishermen include wounds on feet and hands, dermatitis, gastritis, fever, acute respiratory infections (ARI), skin fungi, allergies, and skin irritation. Conclusion: The proper implementation of K3 among fishermen is lacking, and occupational health programs in the informal sector are not prioritized. Consequently, related parties have made no special efforts to address occupational health issues for fishermen. Cooperation between fishermen and relevant parties is essential for improving occupational health efforts in the informal fishing sector.